Improved rotor position determination for a sensorless star‐connected PMSM drive using Direct Flux Control. Issue 17 (28th May 2019) - Schuhmacher, Klaus; Grasso, Emanuele; Nienhaus, Matthias
Abstract : A technique for driving a star‐connected PMSM without a position or speed sensor, which is known in the literature as Direct Flux Control (DFC), is described here. This technique is based on voltage measurements at the machine star point and can work even at very low speeds including standstill. The underlying principle of this technique is outlined and an improved position estimation algorithm allowing the exact reconstruction of the direction of maximum inductance is presented. The DFC technique is implemented on a microcontroller board and experimental validation is conducted on a PMSM both for quasi‐static characterisation and for open‐loop driving.